The Role of Social Media Marketing in Enhancing Tourism Experiences in Uganda - John Walter Tusingwire (Uganda Christian University, 2023)
The study examined the role of social media marketing in enhancing tourism experiences in Kampala CBD, Uganda. The study was guided by objectives which included; identifying the social media platforms used by tourism-related businesses in Uganda to promote their services, engage with customers, and share travel experiences, examining the specific tourist attractions, events, and activities that are being promoted on social media platforms in Uganda, evaluating the effectiveness of social media marketing in promoting Uganda’s tourist attractions and engaging with tourists and to identify the challenges associated with social media marketing in Uganda's tourism industry and the possible solutions. The study was carried out using an explanatory research design where both quantitative and qualitative research approaches were used. The data were collected using questionnaires and during the data collection, both purposive and simple random sampling methods were used. A sample size of 36 tour operator companies in Kampala CBD plus the top management of Ministry of Tourism and Uganda Tourism Board respondents were also used in the study. From the findings, it was revealed that Facebook and Twitter are the primary platforms used by tourism-related businesses to promote their services and engage with customers, while Instagram, YouTube, and TikTok are also valued for their specific purposes. The major tourist attractions and activities being promoted on social media include wildlife, culture and traditions, historical sites, adventure activities, religious sites, and festivals. Social media marketing has proven effective in increasing tourists' awareness of Uganda's attractions, influencing their decisions to visit, facilitating engagement and feedback, and aiding in trip planning. However, challenges exist, including a lack of training and expertise, high costs, intense competition for attention, potential reputation damage from negative reviews, the constantly evolving nature of social media, and the difficulty of standing out amidst user-generated content. Finally, the study recommended the need to address the lack of training and expertise among tourism-related businesses in using social media effectively; the study recommends that it is crucial to provide comprehensive training programs. Finally, the study recommended that it is crucial for tourism-related businesses to develop a unique value proposition that differentiates them from competitors.
This is a dissertation.